Associations between coffee consumption and all-cause and cause-specific mortality in a Japanese city: the Takayama study. Issue 14 (20th May 2019) - Yamakawa, Michiyo; Wada, Keiko; Goto, Yuko; Mizuta, Fumi; Koda, Sachi; Uji, Takahiro; Nagata, Chisato
Abstract: Objective: Epidemiological studies suggest that coffee consumption is inversely associated with all-cause and cause-specific mortality. Evidence from studies targeting non-white, non-Western populations is still sparse, although coffee is popular and widely consumed in Asian countries. Design: Population-based, prospective cohort study. We used Cox proportional hazards models with adjustment for dietary and lifestyle factors to estimate associations between coffee consumption and all-cause and cause-specific mortality. Dietary intake including coffee consumption was assessed only at baseline using a validated FFQ. Setting: A Japanese city. Participants: Individuals aged 35 years or older without cancer, CHD and stroke at baseline ( n 29 079) and followed from 1992 to 2008. Results: From 410 352 person-years, 5339 deaths were identified (mean follow-up = 14·1 years). Coffee consumption was inversely associated with mortality from all causes and CVD among all participants, but not from cancer. Compared with the category of 'none', the multivariate hazard ratio (95 % CI) for all-cause mortality was 0·93 (0·86, 1·00) for <1 cup/d, 0·84 (0·76, 0·93) for 1 cup/d and 0·81 (0·71, 0·92) for 2–3 cups/d. The multivariate hazard ratio (95 % CI) for cardiovascular mortality were 0·87 (0·77, 0·99) for <1 cup/d, 0·76 (0·63, 0·92) for 1 cup/d and 0·67 (0·50, 0·89) for 2–3 cups/d. Inverse associations were also observed for mortality from other causes, specifically infectious and digestive diseases. Conclusion: Drinking coffee, even 1 cup/d, was inversely associated with all-cause mortality and mortality from cardiovascular, infectious and digestive diseases.